The Relationship of Chest X-Ray in COVID-19 Patients and Disease Severity in Arifin Achmad General Hospital Riau - Aulia Rahman; Sri Melati Munir; Indra Yovi; Andreas Makmur (Faculty of Medicine Universitas Airlangga, 2021)
Introduction: Coronavirus Disease 2019 (COVID-19) pandemic is caused by SARS-CoV-2 which spreads rapidly throughout the world and causes clinical manifestations in various organs, especially in the lungs. Clinical symptoms arise from asymptomatic, mild, moderate, severe, and critical symptoms in patients with or without comorbid disease. Chest X-ray examination is one of the modalities in the management of COVID-19 which is cheap and easy to do.Methods: This study was performed by analyzing medical record data of confirmed COVID-19 patients from March to December 2020. This study aimed to examine the relationship between chest X-ray and the degree of disease severity.Results: The results showed that from the examined 542 total samples, the highest number was found in the age group of 40-49 years old (23.6%), women (53%), mild degree of COVID-19 (67.9%), normal chest X-ray (54.6%), predominance on the lower zone of the lung, peripheral and bilateral on abnormal chest X-ray, no comorbid (56.3%), hypertensive in comorbid disease (26.6%). There was a significant relationship between chest X-ray and comorbidity towards COVID-19 severity (p = 0.000).Conclusion:Chest X-ray can determine disease severity, therefore it can be used as the first modality for triage and treatment evaluation in COVID-19 patients.